Robotic ultrasound probe for tumor identification in robotic partial nephrectomy: Initial series and outcomes. (26th August 2012) - Kaczmarek, Bartosz F; Sukumar, Shyam; Petros, Firas; Trinh, Quoc‐Dien; Mander, Navneet; Chen, Roger; Menon, Mani; Rogers, Craig G
<x xml:space="preserve">Abstract</x> Objectives: Accurate tumor identification during partial nephrectomy is essential for successful tumor control. Intraoperative laparoscopic ultrasonography is useful for tumor localization, but the ultrasound probe is controlled by the assistant rather than the surgeon. We evaluated our initial experience using a robotic ultrasound probe that is controlled by the console surgeon. Methods: Partial nephrectomy was carried out in 22 consecutive patients between November 2010 and March 2011. A robotic ultrasound probe under console surgeon control was used in all the cases. All patients had at least 1 year follow up. Results: Mean patient age was 59 years and mean tumor size was 2.7 cm. There were six hilar tumors (27%) and 21 (95%) endophytic tumors. Mean R.E.N.A.L. nephrometry score was 6.9 (range 6–9). Mean operative time was 205.7 min and mean warm ischemia time was 17.9 min (range 6–28 min). All patients had negative tumor margins and were free of disease recurrence at a mean follow up of 13 months. Conclusion: The use of a robotic ultrasound probe during partial nephrectomy allows the surgeon to optimize tumor identification with maximal autonomy, and to benefit from the precision and articulation of the robotic instrument during this key step of the partial nephrectomy procedure.